The Effect of Mindfulness-based Cognitive Behavior Therapy in Improving Self-Confidence of Broken Home Students - Rita Kartika Sari; Bagus Abdillah; Abdul Hadi; Faisal Faisal (STAI Hubbulwathan Duri, 2022)
This study aims to determine the effectiveness of cognitive behaviour therapy with mindfulness techniques through group counselling to increase the confidence of high school students who experience a broken home, through experimental research with a single group pretest post-test design. The sample selection in the study was the purposive sampling technique, which obtained 8 samples from 12 populations that became the research sample. Data analysis used the Wilcoxon test to determine the increase in self-confidence before and after the intervention and the Mann Withney U Test to determine the differences between the intervention groups. The results of experiments that have been carried out show an increase in the self-confidence of students who experience a broken home after being given group counselling on cognitive behaviour therapy with mindfulness techniques.